The Role of French Algeria in American Incorporation of the Philippines and Puerto Rico. Issue 3 (1st December 2022) - Roberts, Tim
Abstract: This article argues that France's conquest and subsequent legal treatment of Algeria as an integral part of France, though without French citizenship for Algerians, served as a transnational precedent for US incorporation of former Spanish colonies in the early twentieth century. While the United States also drew lessons from British colonial policy, as scholarship has shown, France's republican empire offered particular tools, which scholars have not studied, for US courts to designate Filipinos and Puerto Ricans like French Algerians. In essence, French Algeria provided an example for US jurists to create an imperial category for new territorial peoples as neither US citizens nor foreign subjects but as "nationals." The article draws principally on the so-called Insular Cases, US newspapers, and political documents. The article exposes transnational connections between the United States and France in constructing empires of white freedom, no less important than imagined Anglo-Saxonism at the time.